Borboletas frugívoras em dois estratos verticais na Floresta Nacional do Tapajós, Pará, Brasil - LOPES, Aracely Liberal (Universidade Federal do Oeste do Pará, 2021)
One of the most important components influencing the diversity of tropical forests is the vertical stratification. Thus, the richness, abundance and composition of the butterfly fauna can be differentiated in the strata, by their intrinsic relations as the availability of food resources, amount of sunlight, predation pressure and other climatic factors. The fruit-feeding butterflies are especially diverse in these forests and sensitive to changes in the environments they inhabit, responding to the changes that occur in them. In this context, this study investigated the diversity, richness and abundance of frugivorous species belonging to Nymphalidae in two strata in the Tapajós National Forest, from December 2011 to November 2012, using traps allocated in the canopy and understory baited with fermented banana. We evaluated the following parameters: richness, abundance, dominance, constancy, diversity index and evenness (Shannon H 'and E') and Berger-Parker dominance (d). The richness estimates were made using the nonparametric procedures: Bootstrap, Chao1, Chao2, Jackknife1 and Jackknife2. We recorded 1,122 individuals belonging to 90 species, 23 species collected in both strata, 37 exclusively in the understory and 30 only in the canopy. The richness (S), diversity (H ') and abundance (N) were, respectively: in the understorey (S = 60, H' = 3.08, N = 668), canopy (S = 53; H '= 3.19; N = 454). The genus Taygetis was the most abundant in the understory and canopy in Memphis genus. . Was recorded threatened species Agrias narcissus tapajonus (Fassl, 1921) and richness estimates showed a collection representative of the total species expected for each stratum. The results can serve as a basis for strategies for monitoring environmental health and conservation in the Tapajós National Forest. The richness estimates showed that much of the expected total species for each stratum was collected.